Protection of Personal Data of Consumers Using Financial Technology Services - Nugraha, Nurul Jaya; Wardana Mamonto, Andry Wikra; Ilham, Muhammad Azham (Faculty of Law, Universitas Muslim Indonesia, 2025)
This research aims to examine and analyze legal provisions related to the protection of personal data of customers using financial technology services in Indonesian laws and regulations. Apart from that, this research also aims to compare the legal protection of consumer personal data in the regulations in force in Indonesia with the regulations in force in the United States. This research applies normative legal research methods. The data used comes from literature studies, including primary legal materials such as laws, Financial Services Authority Regulations (POJK), and Bank Indonesia Regulations (PBI), as well as secondary legal materials such as laws books and legal journals. The research results show that legal protection for the personal data of consumers using financial technology services in Indonesia has been regulated in Law Number 27 of 2022 concerning Personal Data Protection. This regulation reflects a progressive approach to law, which not only supports the use of technology but also provides protection for users to achieve legal certainty. Meanwhile, a comparison with regulations in the United States shows that personal data protection in the financial technology sector is based on the principle of “right to be alone” which is the main pillar of individual privacy. This principle emphasizes that privacy is a constitutional right of every citizen, as a form of respect and protection for this right.